The synthesis of wiener-davis filter - Єрмолаєва, О. В.; Сив’юк, Д. В.; Пікалюк, Р. В. (Problems of Informatization and Control, 2015)
The algorithm and the results of the synthesis procedure of Wiener-Davis filter, that allows to find thebest structure for a wide class of linear systems are presented in this work. Effectiveness of theproposed algorithm of synthesis is considered in terms of analytical example